Defaunation and biomass collapse of mammals in the largest Atlantic forest remnant - Galetti, M. [UNESP]; Brocardo, C. R. [UNESP]; Begotti, R. A. [UNESP]; Hortenci, L. [UNESP]; Rocha-Mendes, F. [UNESP]; Bernardo, C. S.S. [UNESP]; Bueno, R. S. [UNESP]; Nobre, R. [UNESP]; Bovendorp, R. S. [UNESP]; Marques, R. M. [UNESP]; Meirelles, F. [UNESP]; Gobbo, S. K. [UNESP]; et al. (Wiley, 2017)
Large continuous rainforests are the main hope for sustaining the population of large-bodied vertebrates that cannot cope with fragmentation or unsustainable hunting. The Brazilian Atlantic forest is considered a biodiversity hotspot and although highly fragmented, it still contains large forest patches that may be important for the conservation of mammals that require large areas. Here, we estimated species richness, density and biomass of medium- and large-sized mammals along the largest remnant of the Atlantic rainforest, Brazil (the Serra do Mar bioregion), an estimated area of 8000 km2. We recorded 44 species based on 4090 km of diurnal line transects and camera traps, animal tracks and interviews in 11 continental regions and two large land-bridge islands. We found high levels of similarity in mammalian composition between pairs of sites in the continental forest sites (0.84–1), but much lower similarity between pairs from the continental forest sites and the two large land-bridge islands (0.29–0.74) indicating potential local extinctions or poor dispersal of continental mammals to these islands. In addition, we found that the density and biomass varied 16- and 70-fold among sites, respectively. Mammalian biomass declined by up to 98% in intensively hunted sites and was 53-fold lower than in other Neotropical non-fragmented forests. Although this large forest remnant is able to maintain a high diversity of medium- and large-bodied mammal species, their low density and biomass may affect the long-term persistence of these populations and the ecosystem services they provide.
Keywords: Brazilian Atlantic forest; defaunation; distance sampling; extinction risk; hunting; line-transect method; mammalian communities; protected areas